2017
DOI: 10.5222/buchd.2017.045
|View full text |Cite
|
Sign up to set email alerts
|

Defining teachers’ situation of liking children: Kars province example

Abstract: ÖZAile ve okul ortamında sevgiyle karşılaşan çocuklar gelecekte daha huzurlu bir ortam sağlanmasında önemli rol oynayabilirler. Bu çalışmada, ilk ve ortaöğretim kurumlarında öğretmenlerin çocuk sevme durumlarının belirlenmesi, bu durumun erkek ve kadın öğretmenler arasında bir farklılık gösterip göstermediğinin belirlenmesi amaç-lanmaktadır. Çalışmanın örneklemini, ilköğretim kurumlarından 155, ortaöğretim kurumlarından 314 ve diğer eğitim kurumlarından 21 olmak üzere toplam 500 öğret-men oluşturmuştur. Bu öğr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…At the end of his study, Çay (2015) found that female pre-service teachers' level of liking for children was higher than male pre-service teachers, but the status of liking children did not differ according to the gender of teachers. Türk, Kardaş Özdemir & Kerimoğlu Yıldız (2017) found in their study that being a male or female teacher in terms of gender did not cause a significant difference in terms of liking children. In the light of these findings, it is understood that although the levels of liking children have different results according to gender, the attitude scores of female teachers are higher in tendencies towards love pedagogy.…”
Section: Discussion and Resultsmentioning
confidence: 82%
“…At the end of his study, Çay (2015) found that female pre-service teachers' level of liking for children was higher than male pre-service teachers, but the status of liking children did not differ according to the gender of teachers. Türk, Kardaş Özdemir & Kerimoğlu Yıldız (2017) found in their study that being a male or female teacher in terms of gender did not cause a significant difference in terms of liking children. In the light of these findings, it is understood that although the levels of liking children have different results according to gender, the attitude scores of female teachers are higher in tendencies towards love pedagogy.…”
Section: Discussion and Resultsmentioning
confidence: 82%
“…Ayrıca, öğretmenlerin çocuk sevme konusuna İ. ŞENGÖZ TOSUN, N. S. ERKAN ilişkin çok az çalışma yapılmıştır. Yapılan alanyazın incelemesinde, öğretmenlerin çocuk sevme durumlarına etki eden faktörlerin belirlenmesine ilişkin bazı çalışmalar olduğu görülse de 14 , çocuk sevme özelliğine sahip olmanın daha ön planda olması gereken okul öncesi öğretmenlerinin çocuk sevme durumlarına etki eden faktörleri araştıran çalışmalar bulunmaktadır. Bu noktadan hareketle bu çalışma, küçük çocukların sosyal-duygusal, bilişsel ve kişilik gelişiminde kritik bir önemi olan okul öncesi öğretmenlerinin çocuk sevme durumlarının belirlenmesinin önemli olduğu düşünülerek planlanmıştır.…”
unclassified